Michel Cole - Rosa Rivero, Alberto (1985)
Michael Cole is a professor at the Department of Psychology and Communications in California University, San Diego, (UCSD). He could be regarded as one of the most interesting personalities of American psychology and one of the most remarkable responsables of the difussion and evolution of the Vygostkian school in the United States. In this interview, Professor Cole reflects on the principles of his approach to Culture and Communication psychology; the links between science and society and some other main issues in contemporary psychology, as well as briefly reporting on his training history as a psychologist in the USA and his time in the Soviet Union.